Alteration of C-MYB DNA binding to cognate responsive elements in HL-60 variant cells. Issue 5 (1st October 2002) - Gaillard, C; Le Rouzic, E; Créminon, C; Perbal, B
Abstract : Aims: To establish whether the MYB protein expressed in HL-60 variant cells, which are cells resistant to 12-O-tetradecanoylphorbol-13-acetate (TPA) induced differentiation, is able to bind MYB recognition elements (MREs) involved in the transcriptional regulation of myb target genes. In addition, to determine whether alterations in the binding of the MYB protein to MREs affects HL-60 cell proliferation and differentiation. Methods: Nuclear extracts of HL-60 variant cells exhibiting different degrees of resistance to TPA induced monocytic differentiation were used in electrophoretic mobility shift experiments (EMSAs), bandshift experiments performed with labelled oliogonucleotides containing the MYB consensus binding sequences. Results: The MYB protein contained in nuclear extracts from HL-60 variant cells did not bind efficiently to the MYB recognition elements identified in the mim-1 and PR264 promoters. Molecular cloning of the myb gene and analysis of the MYB protein expressed in the HL-60 variant cells established that the lack of binding did not result from a structural alteration of MYB in these cells. The lack of MRE binding did not abrogate the ability of variant HL-60s to proliferate and to undergo differentiation. Furthermore, the expression of the PR264/SC35 splicing factor was not affected as a result of the altered MYB DNA binding activity. Conclusions: Because the MYB protein expressed in HL-60 variant cells did not appear to be structurally different from the MYB protein expressed in parental HL-60 cells, it is possible that the HL-60 variant cells contain a MYB binding inhibitory factor (MBIF) that interferes with MYB binding on MREs. The increased proliferation rate of HL-60 variant cells and their reduced serum requirement argues against the need for direct MYB binding in the regulation of cell growth.